Business models innovation based on crowds: A comparative study - Katarzyna Kubiak; Anna Wzia̜tek-Kubiak (International Journal of Management and Economics, 2019)
With arrival of information technology, interaction between consumers and companies become more common. It has implications for the way business function and for business models. The aim of the paper is to analyze crowdsourcing and compare crowdsourcing business models of three product and content crowdsourcing companies, their common features and differences. These companies differ considerably in many respects. The business model framework used is based on Osterwalder and Pigneur's approach. The paper shows various consequences of using crowds. It shows that having crowds as a key asset implies a necessity to take care of the crowd and network effect before launching a crowdsourcing initiative. The paper gives those involved in crowdsourcing insight about factors crucial for their company and points to where they need to concentrate their resources.
Keywords: M19; M21; O32; 650; open business model innovation; crowdsourcing; crowdsourcing companies